(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of the study was to identify the most effective treatment in the rearing, fattening, and benefit/cost of CHICKENS, resulting in a delicate but statistically reliable task, since the use of techniques coupled with the various required responses covers the expectations in people —readers or entrepreneurs who want to get involved in the poultry sector. The methodology indicates a quantitative investigation, with an application purpose and an explanatory level of depth, developed in an experimental field, the DCA technique is excluded for the manipulation of the weight variable that considers the collected data, which produced four groups of twenty chickens each. one, applying 4 different treatments that use the balanced ones: NUTRIL, ALCÓN, WAYNE, and PROAVES respectively. The type of inference is inductive during the longitudinal temporal period, the population is constituted by the broiler chickens of the BROILER breed, and the eighty samples of them with similar characteristics. As an instrument, the manual recording of the weights was used, and R-Studio analysis. After compliance with the assumptions of normality, homogeneity of variance, and independence, the application of the experimental technique was carried out, and after confirming the existing difference between the means of the treatments, it was sought to define them by applying a comparison between the pairs of treatment given Tukey’s method. Then, with a graph of means, it was concluded that the balanced "PROAVES" showed better results in standing and peeled weight; similarly for higher benefit/cost. Therefore, it is advisable to use last this in case there are economic purposes involved, and if it is desirable to obtain a higher weight in chickens.